Kajian Kualitas Pelayanan Tera Ulang Meter Taksi Pada Unit Pelaksana Teknis Dinas Metrologi Dinas Perindustrian Dan Perdagangan Provinsi Sulawesi Utara - Rahim, Affandi; Goni, John Hein (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The aim of this study is to determine and describe the quality of service of taxi meter re-calibration in Metrology technical service unit North Sulawesi Province. So far, there is no success parameters that can be used as a reference service that the service has been provided by either or even vice-versa. Method used in this study was a qualitative method using a qualitative descriptive approach. The data was collected by observation, interviews and documentation obtained from the informants in this study, namely the five informants as a taxi driver and data was synchronized with the chief executive office of metrology unit, taxi manager, and executive officers re- calibration. Results and discussion showed total of armada taxi meter re- calibration in UPTD Metrologi as much as 315 unist. Total re-calibration in 2011 that qualified for the test on re-calibration statue valid and legal based UU No. 2 tahun 1981 about metrologi legal as much as 268 units, and not qualified as much as 47 units, among 20 armadas deviate from the technical provision, ie mileage shown over allowed toleranted is 4 % of mileage that had been tested so that could harm the consumen taxi users. 17 armadas damaged and in garage. Conclusions in this research is taxi meter company that operating in North Sulawesi Province not obey yet the rule that on law’s requirement except the Blue Bird company as national company that had been applied trade and nexus law. Otherwise the company not applied a tight rules against taxi meter usage so that transaction the drivers between the pasengers use agreement (mouth argo). There are unformity tariff between one company and the other company. So that make the consumen taxi services users confused. This case not justified on UU No. 2 tahun 1981 about Metrology legal. Keywords : Quality of taxi meter Re-Calibration